The Binding Nature of Judicial Plenary Decisions and Their Impact on Peruvian Labor Law - Carrasco Cabezas, Francisco Arturo (Revista de Derecho, 2025)
The Peruvian legal system incorporates diverse judicial pronouncements—ranging from Constitutional Court rulings to Plenary Sessions (Plenos) of the Supreme Court—with varying degrees of binding authority. In labor law, these pronouncements become especially relevant due to the rapid evolution of employment relationships and the need to protect vulnerable workers. This paper examines the mechanisms designed to ensure jurisprudential uniformity: constitutional precedents, Supreme Court casatory precedents, and Judicial Plenary Sessions (Plenos). Particular emphasis is placed on the recent reforms introduced by Law N°. 31591, which grants binding force to Supreme Plenary Agreements, transforming them into a pivotal reference for lower courts. By exploring both the legal framework and practical challenges, the study highlights how judges and litigators must distinguish between truly binding precedents and non-binding guidelines. Furthermore, it stresses the importance of continuous legal training and critical assessment of each case to maintain consistency while allowing for necessary flexibility. Ultimately, the findings underscore that a balanced and well-informed application of precedents not only prevents contradictory decisions but also fortifies the rule of law, promoting a fair and predictable judicial environment that benefits workers, employers, and the broader community.
Keywords: Labor law, jurisprudence, precedents, Plenary Sessions.